The investigation of the deformations of the elastic bodies with thin coating using D-adaptive finite element model - Kossak, О.; Savula, Y. (Фізико-математичне моделювання та інформаційні технології, 2010)
A D-adaptive mathematical model that combines elastic structures with a thin coating is analysed. The main idea of this approach is based on the formulation of the combined model, which allows the use of 3-D elasticity theory model over one part of the domain, and 2-D Timoshenko’s shell model over the other part. The boundary and variation formulation of the D-adaptive model problem are presented. The numerical results are compared with available exact solutions. The numerical results demonstrate the applicability of this approach.